2008
DOI: 10.1186/1472-6882-8-41
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of two South African honeys produced from indigenous Leucospermum cordifolium and Erica species on selected micro-organisms

Abstract: Background: Honey has been shown to have wound healing properties which can be ascribed to its antimicrobial activity. The antimicrobial activity can be effective against a broad spectrum of bacterial species especially those of medical importance. It has also been shown that there is considerable variation in the antimicrobial potency of different types of honey, which is impossible to predict. With this in mind we tested the antimicrobial activity of honeys produced from plants grown in South Africa for thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 18 publications
(21 reference statements)
5
39
0
Order By: Relevance
“…dilution of the honey and gentamicin (10 µg) and amikacin (30 µg) with a few numbers of resistant isolates which is in partial agreement with Adeleke et al (2006). Richard et al (1988) in his study found that aminoglycoside particularly gentamicin and amikacin showed no and little bactericidal activity respectively against the isolates which is in partial agreement with our study, whereas Basson and Grobler (2008) found no such antimicrocidal activity in honey from South Africa, the native place. It has been found that honey is not only sound as a topical healing agent but also has antibacterial and antifungal properties and promotes wound healing with less scar formation (Subrahmanyam et al, 2001;Osman et al, 2003).…”
Section: Discussionsupporting
confidence: 92%
“…dilution of the honey and gentamicin (10 µg) and amikacin (30 µg) with a few numbers of resistant isolates which is in partial agreement with Adeleke et al (2006). Richard et al (1988) in his study found that aminoglycoside particularly gentamicin and amikacin showed no and little bactericidal activity respectively against the isolates which is in partial agreement with our study, whereas Basson and Grobler (2008) found no such antimicrocidal activity in honey from South Africa, the native place. It has been found that honey is not only sound as a topical healing agent but also has antibacterial and antifungal properties and promotes wound healing with less scar formation (Subrahmanyam et al, 2001;Osman et al, 2003).…”
Section: Discussionsupporting
confidence: 92%
“…Although there are innumerable sources of honey around the world, there seems to be a general consensus that manuka, originating from Australia and New Zealand where at least 79 species of Leptospernum have been described (Thompson, 1988), is the most noteworthy. Scientists from countries as diverse as Nigeria (Efem, 2009), Malaysia (Tan et al, 2009), South Africa (Basson and Grobler, 2008) and Iran (Jalali et al, 2007) have all recently commented on the anti-infl ammatory, anti-allergenic, antibacterial, debriding and cost-effectiveness of particular types. These disparate honeys do not appear to have the remarkable antibacterial effects of manuka, with other honeys varying by as much as 100-fold in antibacterial potency (Simon et al, 2008).…”
Section: Honeymentioning
confidence: 98%
“…methylglyoxal, the substance responsible for the marked in vitro antimicrobial activity of the mānuka honey from Leptospermum scoparium and L. polygaliforlium), bee defensin-1, florally derived phenolics, lysozyme, pinocembrin, lysozyme, phenolic acids, terpenes, benzyl alcohol and other substances which have not been determined fully yet. This antimicrobial activity however varies strongly and depends on the floral source (whose chemical compounds may increase or decrease this activity) and the processing and eventual dilution of the honey (Baas & Grobler, 2008;Bang et al, 2003;Snowdon & Cliver 1996). The floral source itself may also be subjected to changes, e.g.…”
Section: 1general Considerationsmentioning
confidence: 98%